2014
DOI: 10.1016/j.medici.2014.09.005
|View full text |Cite
|
Sign up to set email alerts
|

The significance of reduced glutathione and glutathione S-transferase during chemoradiotherapy of locally advanced cervical cancer

Abstract: The results suggest that changes in the concentration of GSH during the treatment of locally advanced cervical cancer might be important for the prediction of the efficacy of the treatment. Statistically significant changes in GST concentration levels during the treatment were not observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
4
0
1
Order By: Relevance
“…Greater numbers of specimens would be necessary to confirm this finding. High mRNA expression levels of LRP and GSTP1 may mediate drug resistance of tumor cells to cisplatin, suggesting that primary MDR of CC to cisplatin may be associated with the expression levels of LRP and GSTP1 genes (18).…”
Section: Discussionmentioning
confidence: 99%
“…Greater numbers of specimens would be necessary to confirm this finding. High mRNA expression levels of LRP and GSTP1 may mediate drug resistance of tumor cells to cisplatin, suggesting that primary MDR of CC to cisplatin may be associated with the expression levels of LRP and GSTP1 genes (18).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, reduced GSH levels are associated with patient's response to treatment . Predictive role of GSH for patients with CC undergoing chemoradiotherapy is also shown by Daukantienė et al and Vidyasagar et al Srivastava et al demonstrated that increased lipid peroxidation and reduced levels of GSH, SOD, Vitamin A, and E in patients with CC are significantly associated with tumor stage, suggesting their clinical significance as prognostic markers . In contrast, Sharma et al reported higher levels of GSH in patients with CC following chemotherapy .…”
Section: Diagnostic and Predictive Value Of Oxidative Stress Status I...mentioning
confidence: 89%
“…Our own data also suggest that ionizing radiation leads to an enhanced consumption of glutamine 24 h after radiation, 110 most likely as a response to oxidative stress to generate more glutathione 212 (Figure 4). There is also evidence that glutathione levels are increased by radiation in the context of cancer 57,214 . In addition to glutamate, glutathione is made from cysteine and glycine, the latter of which can either be imported or synthesized from serine.…”
Section: Changes To Major Metabolic Pathways Induced By Ionizing Radiationmentioning
confidence: 99%